Serum cytokine profiles in patients with chronic obstructive pulmonary disease associated pulmonary hypertension identified using protein array. (November 2018) - Zhang, Yi; Lin, Peiyi; Hong, Cheng; Jiang, Qian; Xing, Yue; Tang, Xiaoyan; Jiang, Huilin; Luo, Shuhong; Chen, Xiaohui
Highlights: MCP-4, SDF-1 alpha, CCL28, Adipsin, IL-28A, CD40 and AgRP were uniquely altered in COPD patient serum with PH. CCL28, MCP-4, CD40, AgRP and IL-28A were differentially expressed in COPD patients with PH. MCP-4 and CCL28 were clinically validated increase and CD40 decrease in COPD with PH. These cytokines may serve as novel biomarkers for the diagnosis and prognosis of COPD associated pulmonary hypertension. Abstract: Pulmonary hypertension (PH) is a common complication of chronic obstructive pulmonary disease (COPD) and is a significant risk factor for hospitalization and shortened life expectancy. Therefore, developing new serum biomarkers for early diagnosis and prognosis of COPD associated PH is crucial. In the present study, a solid-phase antibody array simultaneously detecting multiple proteins was used to search specific COPD associated PH biomarkers, with COPD patients and healthy subjects as control groups. As a result, compared to the COPD and healthy groups, the levels of MCP-4, SDF-1 alpha, CCL28, Adipsin, IL-28A, CD40 and AgRP were uniquely altered in COPD patient serum with pulmonary hypertension. Among these proteins, CCL28, MCP-4, CD40, AgRP and IL-28A were identified to be differentially expressed in COPD patients with hypertension, indicating that these cytokines may serve as novel biomarkers for the diagnosis and prognosis of COPD associated pulmonary hypertension.